Analytical modeling and experimental validation of workpiece temperature variation in bull-nose end milling. Issue 1 (September 2016) - Yan, R.; Zeng, H.; Peng, F.; Yang, S.; Dong, Q.; Zhou, L.
Abstract A thermal model that reveals workpiece temperature variation in bull-nose end milling is presented in this paper. Both machining history and cutting tool are discretized into elements to tackle the problems of interrupted cutting process and complex cutter geometry. In the proposed modeling methodology, shear plane heat source is considered as moving instantaneous rectangular heat source. Image heat source is applied to deal with boundary issues of heat conduction in workpiece. The proposed model is validated by machining 300 M steel under dry cutting state. Good agreement between the estimated and measured workpiece temperatures indicates that the analytical model can provide accurate predicted results. The effects of spindle speed and feed rate on workpiece temperature are theoretically and experimentally investigated. Some conclusions of this study are summarized as follows: (1) In the studied range of processing parameters, workpiece temperature increases with increasing spindle speed and decreases with increasing feed rate. (2) Temperature in workpiece under stable milling state decreases exponentially with increasing horizontal distance between inner point and machined surface.